Women’s Resilience and Vulnerability in Facing COVID-19 in DKI Jakarta and East Java - Ashilly Achidsti; Oktafia Kusuma Sari; Desy Putri Ratnasari; Nourmalita Safitri Ningsih; Aulia Reski Widyaningrum; Jaler Sekar Maji; Muhammad Uwais Sidhi Weiss; Sahal Sabilil Muttaqin (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2020)
Indonesia ranks 23rd as the most COVID-19 confirmed cases in the world. DKI Jakarta and East Java provinces have the highest cases in Indonesia. However, data on the transmission of COVID-19 in both provinces were not further analyzed regarding vulnerability between genders. This research attempted to compare the differences in the gender distribution of COVID-19 cases by analyzing data from COVID-19 DKI Jakarta and East Java Task Force Information Center and various biological, medical, and socio-cultural studies to understand risk of women being exposed to COVID-19. The results of this research revealed that both provinces had a higher number of confirmed patients under surveillance (PDP), people under surveillance (ODP), and death cases in men than that of women. In DKI Jakarta, the number of recovered cases in men was higher than that of women, but in East Java it was not significantly different. Based on literature reviews, women were more resilience in manifestations of COVID-19 severity than that of men due to differences in ACE2 gene distribution and expression, hormones regulations, immune responses, comorbidities, and ages. However, data from socio-cultural literature reviews in both provinces showed women were vulnerable to be exposed to COVID-19 since many women performed as health workers, office workers, market traders, public transportation users, and did religious activities. Besides, women were vulnerable due to mental health condition, such as depression, anxiety, and special medical condition (e.g. being exposed to or infected with COVID-19 during pregnancy).